2021
DOI: 10.1101/2021.03.02.433550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human stem cell-based retina-on-chip as new translational model for validation of AAV retinal gene therapy vectors

Abstract: Gene therapies using adeno-associated viruses (AAVs) are amongst the most promising strategies to treat or even cure hereditary and acquired retinal diseases. However, the development of new efficient AAV vectors is slow and costly, largely because of the lack of suitable non-clinical models. By faithfully recreating structure and function of human tissues, human induced pluripotent stem cell (iPSC)-derived retinal organoids could become an essential part of the test cascade addressing translational aspects. O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As directly inserting the gene of interest into target cells would not result in expression of the gene, it is delivered by an engineered carrier called a vector. The commonly used vectors include certain modified viruses that deliver the gene through infection [7][8][9]. For example, when retroviruses infect the target cell, they insert their genetic material (such as the new gene) into the cell's genome, whereas when adenoviruses infect the cell, they deliver their DNA into the nucleus but not into a chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…As directly inserting the gene of interest into target cells would not result in expression of the gene, it is delivered by an engineered carrier called a vector. The commonly used vectors include certain modified viruses that deliver the gene through infection [7][8][9]. For example, when retroviruses infect the target cell, they insert their genetic material (such as the new gene) into the cell's genome, whereas when adenoviruses infect the cell, they deliver their DNA into the nucleus but not into a chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2021, there are several publications describing the results of experiments on transduction of organoids derived from lungs, [ 85 ] retina, [ 44,86,87 ] brain, [ 88–90 ] intestine, [ 43 ] and liver [ 91 ] using rAAV vectors. The studies revealed a number of limitations associated with the specifics of cultivation and the cellular composition of organoids, which can obstruct their effective transduction.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some types of organoids, such as retinal ones, can be cultured in a liquid medium without matrix support. In this case, no additional manipulations are required for the rAAV transduction, [ 86,87,104 ] the viral vector preparation is introduced directly into the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…AAV2/5 under the CAG promoter transduced photoreceptors with high efficiency (~ 90%) and was used to rescue RP2 expression in RP2-KO retinal organoids, improving photoreceptor survival [ 71 ]. On the retina-on-chip model, the AAV2-7m8 variant was also more efficient at transducing mature photoreceptors, Müller, and ganglion cells, compared to first-generation AAV variants [ 72 ]. The newly generated recombinant AAV vectors AAV2.NN and AAV2.GL outperform AAV2 and AAV2-7m8 in mice and are able to effectively transduce human retinal explants [ 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…The newly generated recombinant AAV vectors AAV2.NN and AAV2.GL outperform AAV2 and AAV2-7m8 in mice and are able to effectively transduce human retinal explants [ 73 ]. In organoids, the variant AAV2.GL had a comparable transduction efficiency to AAV2-7m8, while AAV2.NN had higher fluorescence levels than all other AAV variants tested [ 72 ]. The NN peptide-insert also showed high transduction efficiency of organoids when used in the AAV9 vector [ 74 ].…”
Section: Introductionmentioning
confidence: 99%